ANALISIS CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP RETURN SAHAM DAN NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE (GCG) SEBAGAI PEMODERATING - Ria Manurung (Jurnal Keuangan dan Bisnis, 2019)
This research was conducted to obtain results or output empirically to test the effect of corporate social responsibility (CSR) on stock returns and the value of companies with good corporate governance as moderating. This study examines manufacturing companies that have been registered with the Indonesia Stock Exchange (IDX) for the 2015-2017 period. A total of 539 manufacturing companies were used as populations with purposive judgment sampling as a sampling method. The method used in this study is the method of documentation carried out by collecting secondary data published by companies on the Indonesia Stock Exchange in the form of annual reports. This research is a quantitative study with a correlational analysis method to examine the effect of independent variables on the dependent variable. The results of this study are H1, H2, and H3 accepted, so there is a partial influence on the variables of CSR, GCG and CSR and GCG simultaneously. So that the greater CSR with GCG support, the greater the potential to increase stock returns and company value.